Alkaline sill intrusions in sedimentary basins: emplacement of the Mussentuchit Wash Sill in San Rafael Swell, Utah. Issue 1 (2023) - Kjenes, Martin; Eide, Christian Haug; Schofield, Nick; Chedburn, Lauren
No abstract available